Saving capitalism from short-termism : how to build long-term value and take back our financial future - Rappaport, Alfred (New York : McGraw-Hill, 2011)
'Now is the time to redirect your focus from short-term gain to long-term growthAlfred Rappaport, who first introduced the principles and practical application of'shareholder value' in his groundbreaking 1986 classic Creating Shareholder Value, reiterated the basic message in his 2006 Harvard Business Review article: Focusing on Wall Street quarterly earnings expectations rather than on creating long-term value is an invitation to disaster. Rappaport shows how deeply flawed short-term performance incentives for corporate and investment managers were an essential cause of the recent global financial crisis. In Saving Capitalism from Short-Termism, Rappaport examines the causes and consequences of'short-termism' and offers specific recommendations for how publicly traded companies and the investment management community can overcome it. Whether you're a corporate manager, money manager, public policymaker, business-school student, or simply concerned about your financial future, Saving Capitalism from Short-Termism provides valuable insights and practical ideas to change the course of your organization --and contribute to a healthier economy that benefits all'--Provided by publisher.
Keywords: Investment analysis; Capitalism